International market screen for industry clusters : a theoretical approach for governments - Tan, James Teng Chuan (2008)
Proposed a two-phase market screening model. The first phase of our model involves screening out countries that do not meet a threshold and we introduce our matrix in the second phase. This matrix allows governments to analyse potential target countries in the context of how easy it is to operate there, how developed the existing factor conditions are, and how the investment fits with their strategies and goals